The effect of TP53 codon 72 and RNASEL codon 462 polymorphisms on the development of cervical cancer in Argentine women - Barbisan, Gisela (2011)
Epidemiological evidence suggests that genetic factors, such as variants in cancer suppressor genes, may play an important role in the etiology of cervical carcinoma. . TP53 is an outstanding cell cycle regulator, mutated in most human cancers, and . RNASEL is thought to be involved in antiviral and apoptotic responses. To determine whether . TP53 Arg72Pro and . RNASEL Arg462Gln polymorphisms are associated with susceptibility to cervical cancer, a case-control study of 98 cancer patients and 123 healthy controls was conducted. Cervical samples were genotyped for both polymorphisms by pyrosequencing technology. The association between cervical cancer risk and the studied SNPs was evaluated by logistic regression, and potential gene-gene interactions were studied by Multifactor Dimensionality Reduction analysis. In the single-locus analysis, only the heterozygous . TP53 Arg72Pro genotype was significantly associated with the risk of developing a cervical carcinoma, while the . RNASEL polymorphism showed no association after age adjustment. In addition, the combination of both polymorphisms gives near-null information gain. Consequently, the effect provided by each single nucleotide polymorphism individually is considered higher than the effect resulting from the interaction between these two genes in cervical cancer risk. These results suggest that a heterozygous . TP53 Arg72Pro genotype may contribute to cervical cancer susceptibility.